Growth hormone deficiency in three siblings homozygous for a rare GH1 haplotype - Ribeiro, Ana Cláudia; Omar, Omneya Magdy; Abdalla, Ebtesam; Lemos, Manuel Carlos (Frontiers in Endocrinology, 2026)
IntroductionGrowth Hormone (GH), secreted by the anterior pituitary gland, is a key regulator of postnatal growth. Mutations in the GH1 gene can lead to isolated GH deficiency (IGHD), a rare disorder characterized by growth failure and severe short stature. The aim of this study was to identify the genetic basis of IGHD in three siblings born to consanguineous parents.MethodsThree siblings were diagnosed with short stature due to GH deficiency (stimulated GH peak levels between 0.07 and 0.77 µg/L). To identify their genetic cause, whole-exome sequencing (WES), multiplex ligation-dependent probe amplification (MLPA), and targeted GH1 sequencing was performed.ResultsA shared homozygous GH1 haplotype comprising nine single nucleotide polymorphisms (SNPs), spanning the promoter, coding, and 3’ flanking regions, was revealed. The parents were heterozygous carriers of this haplotype. This rare SNP combination (with less than 1% population frequency) overlaps with transcriptional regulatory elements and has previously been associated with significantly reduced promoter activity (58% promoter activation relative to wild-type). No pathogenic coding mutations or deletions were identified.ConclusionOur findings suggest that this haplotype likely underlies the GH deficiency observed in the affected siblings. This represents the first report linking a homozygous GH1 promoter haplotype to IGHD, underscoring the role of noncoding variants in endocrine disease.